Tumour‐infiltrating lymphocytes in ductal carcinoma in situ (DCIS)—assessment with three different methodologies and correlation with Oncotype DX DCIS Score. Issue 5 (26th September 2020) - Komforti, Miglena; Badve, Sunil S; Harmon, Bryan; Lo, Yungtai; Fineberg, Susan
Abstract : Aims: Tumour‐infiltrating lymphocytes (TILs) are prognostic in invasive breast cancer; however, their prognostic significance in ductal carcinoma in situ (DCIS) has not been established. The Oncotype DX (ODX) Breast DCIS Score test is a genomic assay used to predict the local recurrence risk. The aims of this study were to quantify TILs in DCIS by the use of three methodologies, and correlate them with the ODX DCIS Score. Methods and results: We studied 97 DCIS cases, all with an ODX DCIS Score. Cases with a low ODX DCIS Score were considered as one group, and those with an intermediate/high ODX Score were considered together. TILs were quantified on haematoxylin and eosin‐stained slides. The methodologies used to quantify TILS included assessment of stromal TILs, assessment of touching TILs, and assessment of circumferential TILS. In cases with >5% stromal TILS, the percentage of stromal TILS was considered to be high. In cases with a mean number of more than five touching TILs per DCIS duct, TILs were considered to be present. The ODX DCIS Score was intermediate/high in 27 (28%) cases and low in 70 (72%) cases. There were >5% stromal TILs in 33 (34%) cases, and more than five touching TILs per DCIS duct in 15 (15%) cases; circumferential TILs were present in nine (9%) cases. In univariate analysis, a low ODX DCIS Score showed significant associations with absent touching TILS ( P  = 0.027), stromal TILs < 5% ( P  = 0.031), and absent circumferential TILs ( P  = 0.002). In logistic regression analysis adjusted for necrosis and nuclear grade, touching TILs and circumferential TILs showed significant associations with the ODX DCIS Score, whereas stromal TILs did not. Conclusions: Our results suggest that both the presence of TILs and the spatial arrangement of TILs or close proximity of TILs to DCIS, and TILs touching or encircling DCIS, may be predictive of recurrence.